Features of a numerical characteristics estimation for the execution time of complex series-parallel operations - Oleinikova, S A; Bolnokina, E V; Kravets, O Ja (IOP conference series. Materials Science and Engineering, 2019)
The object of research in this paper is stochastic multistage systems, the service process in which a set of series-parallel operations with a random duration of service is performed. The subject of the study is the random variable which is the service time of the entire application. The aim is to evaluate the analytical capabilities to accurately assess the characteristics of the studied value. The possibility of analytically obtaining the characteristics of a random variable is investigated, as a result of which a conclusion is made about the usefulness of connecting numerical apparatus. Thus, the features of estimating the numerical characteristics of a random variable describing the duration of a complex of series-parallel operations are analyzed.